Analisis Perbandingan Teori Konsumsi, Tabungan, dan Investasi dalam Perspektif Konvensional dan Ekonomi Islam - Sagita Wulansari; Ellisa Nazarina; Sabila Hidayatussolikah; Nugraha Esa Saputra; Amalia Nuril Hidayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyse the comparison of consumption, savings, and investment theories in the perspective of conventional and Islamic economics. This research uses a qualitative approach with literature studies from various relevant sources. The results show that conventional consumption theory emphasises income as the main factor in consumption decisions, while Islamic economics considers spiritual aspects, blessings, and social justice. In terms of savings and investment, the conventional approach focuses on capital accumulation and economic growth, while the Islamic perspective emphasises the principle of wealth distribution, the prohibition of usury, and the orientation towards maslahat. This research reveals that the Islamic economic system offers a more holistic and equitable approach to managing consumption, savings and investment.